Gain and noise performances of an L-band EDFA utilizing a ring laser cavity with fiber Bragg grating - Harun, Sulaiman Wadi; Tamchek, Nizam; Ahmad, Harith (John Wiley & Sons, 2002)
The performances of gain and noise figure of an L-band EDFA utilizing a ring laser cavity is demonstrated. It uses a fiber Bragg grating (FBG), arranged to propagate in opposition to the amplifier signal by a pair of circulators, to provide laser feedback. A flat-gain spectrum with less than 1.1-dB variation between 1568 nm and 1604 nm was observed with the laser wavelength at 1560 nm. A gain-clamping effect was also observed with this configuration, which provided a constant gain for all tested input signal powers from -40 dBm to 0 dBm.